Research Progress on the Ion Exchange Treatment and Resource Utilization of Chromium(Ⅵ) Electroplating Wastewater - ZHA Li - na, LI Jin - hua, ZHOU Bao - xue, YUAN Yue - wen, YUAN Hua (Cailiao Baohu, 2021)
From the perspective of resource utilization, the research progress of on - line recovery and in - situ utilization of chromium(Ⅵ) electroplating wastewater was elaborated based on ion exchange technologies, including the selection of ion exchange agents, technological conditions for on - line recycle and in - situ utilization, and countercurrent rinsing technology. These technologies realized the in - situ utilization of heavy metals and water resources in electroplating production line, which was meaningful for controlling the chromium(Ⅵ) electroplating wastewater in the source and process bases.